Fiscal federalism and economic performance: evidence from Swiss cantons - Lars P. Feld; Gebhard Kirchgässner; Christoph A. Schaltegger (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
The advantages and disadvantages of fiscal federalism are widely discussed in economics and political science. While some authors argue that federalism favors individual initiatives and serves as a market preserving device, others emphasize the dangers arising from an increasing corruption and local capture due to decentralization. In this paper, we empirically study the impact of different instruments of fiscal federalism on economic performance measured by GDP per capita using panel data for the 26 Swiss cantons from 1980 to 1998. In our econometric production function approach, the impact of fiscal federalism, tax competition and grants on economic performance is analyzed by additionally using controls for physical and human capital investment as well as further controls and indicators of fiscal federalism. According to our results, the intensity of tax competition, which is measured by the difference between a cantons tax rate and the average of its neighbors tax rates, is at least not harmful for economic performance. Moreover, the fragmentation of cantons in communities does not affect real GDP per capita indicating that economies of scale do not necessarily provide a good argument for a merger of communities.
Keywords: D7; D72; H71; 330; Fiscal Federalism; Economic Performance; Tax Competition; Grants; Finanzföderalismus; Steuerwettbewerb; Finanzausgleich; Regionale Entwicklung; Schätzung; Schweiz